3x+x-7=4x-7

Simple and best practice solution for 3x+x-7=4x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+x-7=4x-7 equation:


Simplifying
3x + x + -7 = 4x + -7

Reorder the terms:
-7 + 3x + x = 4x + -7

Combine like terms: 3x + x = 4x
-7 + 4x = 4x + -7

Reorder the terms:
-7 + 4x = -7 + 4x

Add '7' to each side of the equation.
-7 + 7 + 4x = -7 + 7 + 4x

Combine like terms: -7 + 7 = 0
0 + 4x = -7 + 7 + 4x
4x = -7 + 7 + 4x

Combine like terms: -7 + 7 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 1/2(8x-5)=4x | | -2/v=4 | | 1+5m+2m=15 | | d=70t+100 | | 16x^8-100y^6=0 | | 0=x^2-3x-7 | | N+2-1=-3 | | 0.3s-11.33=12.67+4.3s | | (6w^4)(-w^3)= | | 1+n+4n=6 | | 3x+9=2x-6+4 | | 8x+20=132 | | -4.3+8= | | f(6)=-9 | | 2+(6x-5)=10-(3x-8) | | 7*3x+14=2*3x+79 | | 5b+2a+7=0 | | 3(3x+2)+7=6x+1 | | 2.71a+b=360 | | 60(7x+25)= | | 2a+5b+7=0 | | 3b-5b=-10 | | 3(x+3)+6=4(x+2)+7 | | 8.5x+100=72.25+10x | | a+2.71b=360 | | f(2)=-1 | | 4x-9=(x-6) | | 1-6x-6=13 | | 3(2x+5)-7(3x+6)=5(6x+8) | | c=3.14ford | | -5=-2-2r-5 | | 5.3x+1600=28.09+40x |

Equations solver categories